G125(P) Uk transfusion-associated necrotising enterocolitis cases identified through a multicentre audit. (27th April 2015) - Hamad, S; Jones, K; Sim, K; Cherian, S; James, A; Godambe, S; New, H; Kroll, JS; Clarke, P
Abstract : Aim: Transfusion-associated necrotising enterocolitis (TANEC) has been reported from The Americas and various European countries at rates comprising 27−38% of necrotising enterocolitis (NEC) cases. While the role of packed red blood cell (PRBC) transfusion in causation of NEC remains debated, there are surprisingly few reports of TANEC in the UK setting. Our aim was to analyse the incidence of NEC and TANEC in UK NICUs using uniform definitions. Methods: We undertook a retrospective multicentre audit covering the period October 2011 to November 2014 in four tertiary-level UK NICUs. We assessed whether definite NEC cases (NEC diagnosed surgically via laparotomy, post-mortem, and/or a strict clinical-radiological diagnosis) were also TANEC cases (first onset of NEC symptoms within 48 h of commencement of a PRBC transfusion). Of participating NICUs, three introduced routine probiotic prophylaxis during the study period and one practised routine cessation of enteral feeding during PRBC transfusions. Results: 1608 (20.1%) of 8007 babies admitted in the 38-month study period were very low birth weight (VLBW) and 68 (4.2%) had definite NEC. Of these 15 (22.1%) were TANEC; 34 (50.0%) had received prior PRBC transfusion but were not TANEC; 19 (27.9%) had received no prior PRBC transfusion. Across NICUs, the incidence of definite NEC ranged from 4.5−9.7 cases/year (3.6−7.8 per 100 VLWB admissions) and that of TANEC ranged from 0.50−1.95 cases/year (0.4−1.7 per 100 VLWB admissions). The proportion of TANEC/NEC cases within individual NICUs ranged from 11%−40%. TANEC cases were of median birth weight 695 g (range: 527−1070 g) and birth gestation 25 +1 weeks (range: 23 +2 −27 +0 weeks). Median age at start of the index PRBC transfusion was 18 days (range: 0−69 days). Overall, 12 (80%) required surgical intervention and 9 (60%) survived to discharge. Four (27%) TANEC cases occurred in babies who had received prior probiotics. Conclusion: TANEC occurs in the UK in proximal association with PRBC transfusion at rates similar to those reported from other countries. Rates of NEC and TANEC vary widely between UK centres. A large prospective UK surveillance study is now indicated to improve the understanding of the causation of TANEC.